Colorectal Neoplasia in CDH1 Pathogenic Variant Carriers: A Multicenter Analysis. (6th November 2022) - Stanich, Peter P.; Elgindi, Dareen; Stoffel, Elena; Koeppe, Erika; Bansal, Ajay; Stetson, Rachel; Collins, Debra L.; Clark, Dana Farengo; Karloski, Eve; Dudley, Beth; Brand, Randall E.; Hall, Michael J.; et al.
Abstract : INTRODUCTION: Germline variants in CDH1 are associated with elevated risks of diffuse gastric cancer and lobular breast cancer. It is uncertain whether there is an increased risk of colorectal neoplasia. METHODS: This was a retrospective analysis of colonoscopy outcomes in patients with germline CDH1 pathogenic/likely pathogenic variants. RESULTS: Eighty-five patients were included with a mean age of 46.9 years. Initial colonoscopy found adenomatous polyps in 30 patients (35.3%), including advanced adenomas in 9 (10.6%). No colorectal cancers were identified on index or subsequent colonoscopies (when available). DISCUSSION: CDH1 carriers have colorectal neoplasia identified at similar rates as in the general population. Despite potential difficulties after gastrectomy, colorectal cancer screening remains important in this population.